If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(2x-1) = 11x+5
We simplify the equation to the form, which is simple to understand
7(2x-1)=11x+5
Reorder the terms in parentheses
+(+14x-7)=11x+5
Remove unnecessary parentheses
+14x-7=+11x+5
We move all terms containing x to the left and all other terms to the right.
+14x-11x=+5+7
We simplify left and right side of the equation.
+3x=+12
We divide both sides of the equation by 3 to get x.
x=4
| 2a+7=-2-3 | | H=68t-8t | | (9(y+5)-18)+(3(y-3)+5)= | | 5=7-7x | | p^2+4p+4=40 | | 2x-(x+1)= | | (8y-5)6y-7= | | 4(x+5)5=2x-4 | | 6d-11/2=2d-13/2 | | (X+10)2=y+100 | | 24x+19x=180 | | 7/10x=14/5 | | 17-x=172 | | 70-61x+4x^2=0 | | -3=-6-x | | -24+5x+x^2=0 | | x^3+3x^2-15x=0 | | -24+x^2=0 | | -9(x+9)+4=-77 | | 18000=p(1+.12*2) | | 21y=4(5x-6) | | 7(4s+1)=63 | | 70-16x+4x^2=0 | | 2b=20-28 | | 5c+15=15+4c-2 | | 5+x-4=14 | | 7x+4-2x=5x+4 | | (e^5x+3)-8=0 | | n-45+25-9= | | 2x+6x=-5+7 | | y=.0388ln(x)+.0366 | | 4(x-3)=2x-7 |